Characterization and use of a fiber optic sensor based on PAH/SiO2 film for humidity sensing in ventilator care equipment - Hernandez, Francisco U.; Morgan, Stephen P.; Hayes-Gill, Barrie R.; Harvey, Daniel; Kinnear, William; Norris, Andrew; Evans, David; Hardman, J.G.; Korposh, Sergiy (IEEE, 2016)
Objective: To develop a compact probe that can be used to monitor humidity in ventilator care equipment. A mesoporous film of alternate layers of Poly(allylamine hydrochloride) (PAH) and silica (SiO2) nanoparticles (bilayers), deposited onto an optical fibre was used. The sensing film behaves as a Fabry-Perot cavity of low-finesse where the absorption of water vapour changes the optical thickness and produces a change in reflection proportional to humidity. Methods: The mesoporous film was deposited upon the cleaved tip of an optical fibre using the layer-by-layer method. The sensor was calibrated in a bench model against a commercially available capacitive sensor. The sensitivity and response time were assessed in the range from 5 % relative humidity (RH) to 95 %RH for different numbers of bilayers up to a maximum of nine. Results: The sensitivity increases with the number of bilayers deposited; sensitivity of 2.28 mV/%RH was obtained for nine bilayers. The time constant of the response was 1.13 s ± 0.30 s which is faster than the commercial device (measured as 158 s). After calibration, the optical fibre humidity sensor was utilised in a bench top study employing a mechanical ventilator. The fast response time enabled changes in humidity in individual breaths to be resolved. Conclusion: Optical fibre sensors have the potential to be used to monitor breath to breath humidity during ventilator care. Significance: Control of humidity is an essential part of critical respiratory care and the developed sensor provides a sensitive, compact and fast method of humidity monitoring.